Alternative and Improved Stability-Indicating HPLC Method for the Assay of Eprinomectin and Determination of Its Related Compounds in Bulk Batches of Eprinomectin Drug Substance. (6th May 2021) - Padivitage, Nilusha; Tian, Jingzhi; Rustum, Abu
Abstract: Background: Eprinomectin is used as an active pharmaceutical ingredient (API) in various drug products by the animal health industry. Several major related impurities of eprinomectin API are not separated and coelute by the current United States Pharmacopeia (USP) method for eprinomectin. Objective: The aim was to develop and validate a true and reliable stability-indicating reversed-phase (RP) HPLC method for assay and determination of related substances of eprinomectin in bulk batches of eprinomectin API. Method: HPLC analysis is carried out using a Kinetex C8 column (100 mm × 4.6 mm i.d., 2.6 μm particle size) maintained at 30°C with water–acetonitrile–isopropanol (48 + 42 + 10, v/v/v) as mobile phase A and 100% acetonitrile as mobile phase B. Analytes are separated by gradient elution at a flow rate of 0.7 mL/min and detected by UV at 252 nm. The total run time of the method is 30 min. Eprinomectin assay and estimation of all eprinomectin-related substances are obtained in a single HPLC run. Results: The HPLC method was able to separate all analytes of interest by gradient elution. The new method was successfully validated according to current The Internal Council for Hamonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH) and International Cooperation on Hamonisation of Technical Requirements for Registration of Veterinary Medicinal Products (VICH) guidelines and was found to be specific, linear, accurate, precise, robust, and sensitive. Conclusions: An HPLC method for assay of eprinomectin and estimation of its related substances was successfully developed, validated, and demonstrated to be accurate, robust, specific, and stability-indicating. Highlights: The HPLC method presented in this paper is more desirable as compared to USP and suitable for routine analysis of bulk batches of eprinomectin API and stability samples in QC laboratories.